Assessment of tensile behavior and failure mechanism in the two integrated composite joints. (November 2021) - Du, Yong; Ma, Yu'e; Wang, Zhaohui; He, Yanli; Wang, Zhenhai
Highlights: Two different integrated composite joints are tested and studied. The ultimate failure load of joint A is two times higher than that of joint B. Damage initiation and propagation of the skin of these both joints are same. FEA correctly predicts the location of initial damage in the two joints. Effects of stacking sequence and thickness on tensile behavior are analyzed. Abstract: In order to study tensile behavior and failure mechanism of the integrated composite joints of the skin, the longeron and the frame in fuselage structure, the adhesively bonded (joint A) and the mechanically fastened (joint B) integrated composite joints were designed and manufactured. Tensile tests were performed for both joints. The strain versus load curves and the load versus displacement curves were measured, analyzed and compared. It is shown that the first drop load and the ultimate failure load of joint A are 120.82kN and 168.11kN, respectively. While the first drop load and the ultimate failure load of joint B are 41.05kN and 68.22kN. The finite element models for both joints had been established to simulate and analyze failure mechanisms, interlaminar damage behaviors and effects of design parameters on mechanical properties. The dominant failure modes are delamination and interface debonding, which caused by the weak interlaminar strength between joint components. Damage initiation of joint A occurs at the corner bend region of the corner-stiffened laminate around the filler, and then propagates along the radius bend region of the corner-stiffened laminate, and finally leads to the interface debonding and the delamination in the interface of both stiffeners of joints. Damage initiation and propagation occurred at the center of the skin and the L-stiffened laminates of joint A. While for joint B, damage initiation and propagation of the corner-stiffened laminates and the L-stiffened laminates were changed because of the holes. The strength of joint A is two times higher than that of joint B, whether the stacking sequence and the thickness changes or not.